2009
DOI: 10.1021/om900925b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Coordination Chemistry, and Catalysis of the First 1,2-Bis(diphenylphosphino)-1,2-diphenylhydrazine, Ph2PN(Ph)N(Ph)PPh2

Abstract: The reaction of chlorodiphenylphosphine with dilithiohydrazobenzene gave 1,2-bis(diphenylphosphino)-1,2-diphenylhydrazine, [PPh 2 N(Ph)N(Ph)PPh 2 ] (1). Treatment of 1 with NiCl 2 (DME), PdCl 2 (PhCN) 2 , and PtCl 2 (COD) resulted in the formation of complexes of the type cis-[MCl 2 -{Ph 2 PN(Ph)N(Ph)PPh 2 }] (M = Ni (3), Pd (4), Pt ( 5)). The molecular structures of the starting ligand 1 and the complexes 3, 4, and 5 have been determined by X-ray diffraction. The ligand 1 and its Ni(II) complex 3 were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…Both Ni1–Cl distances [Ni1–Cl1 = 2.2060(8) Å, Ni1–Cl2 = 2.1846(8) Å] conform values for other Ni(PPhNR) 2 Cl 2 compounds (Ni–Cl range from 2.1838 Å to 2.209 Å) as published by Ghosh et al, Rosenthal et al, and Daly et al…”
Section: Methodssupporting
confidence: 75%
“…Both Ni1–Cl distances [Ni1–Cl1 = 2.2060(8) Å, Ni1–Cl2 = 2.1846(8) Å] conform values for other Ni(PPhNR) 2 Cl 2 compounds (Ni–Cl range from 2.1838 Å to 2.209 Å) as published by Ghosh et al, Rosenthal et al, and Daly et al…”
Section: Methodssupporting
confidence: 75%
“…The chemical shifts of these doublets in 2a-d were all very similar and at approx. δ −21 (PCH 2 ) and δ 68 (PN) ppm 10,14 indicating that small changes in the R 1 aromatic substituent have negligible effect on the electronic properties of the P nuclei. The absence of an NH resonance in the 1 H NMR spectra and of a ν(NH) stretch in the IR spectra confirmed that the amine group has successfully been replaced by a -PPh 2 group.…”
Section: Unsymmetrical Bidentate Aminomethylphosphinesmentioning
confidence: 99%
“…10 Inspired by these findings, chemists have sought to explore the scope of Group 15/16 ligands for Cr-catalysed ethylene oligomerisations 11,12 and polymerisations. 13 Some examples of P-based ligands studied, for ethylene tri-/tetramerisations, highlight the vari-ation of backbone groups including -NN-, 14,15 -CC- 16,17 and -NSi-(shown in Chart 1). 18 Whilst significant advances in ligand design have aided catalyst performance, there have also been considerable computational [19][20][21][22] and mechanistic [23][24][25] efforts to probe the nature of catalytically important Cr-based intermediates, and the origin of 1-hexene and 1-octene selectivities.…”
Section: Introductionmentioning
confidence: 99%
“…For comparison purposes, the Ni(0) complex [Ni{Ph 2 PN( i Pr)P(Ph)NH( i Pr)‐ P,P′ } 2 ], the M(II) complexes cis ‐[NiX 2 {Ph 2 PN( i Pr)P(Ph)NH( i Pr)‐ P,P′ }] with M=Ni, Pd, Pt, X=Cl or Br and the iron complex trans ‐[Fe(CH 3 CN) 2 {Ph 2 PN( i Pr)P(Ph)NH( i Pr)‐ P,P′ } 2 ](BF 3 ) 2 were prepared. In all of these complexes, by coordination of both P atoms four membered M−P−N−P metallacycles were formed with no interaction between the metal and the N atoms.…”
Section: Resultsmentioning
confidence: 99%